Diagnosis of water supply services from the perspective of the user in the city of Ibateguara-AL / Diagnóstico dos Serviços de Abastecimento de água na Perspectiva do Usuário na Cidade de Ibateguara-AL - Sirlange Soares da Silva Brito; Eliene Oliveira da Silva; Claudionor de Oliveira Silva (Universidade Estadual de Alagoas, 2019)
The objective of this work was to analyze the water supply systems in the municipality of Ibateguara / AL. The type of research is qualitative and quantitative, first started as bibliographical research, laws, ordinances; with the main theoretical references, such as Adede y Castro (2008), Janine (2010), Tucci (2001), among other scholars on issues related to the problem involving water and its supply systems, in addition to the analysis of Law No. 9,433 / 97, which deals with the National Policy on Water Resources, Law 5965/97, which deals with the State Policy on Water Resources, which aims to ensure the control of water use and its use, in quantity, quality and satisfactory regime, by its current users and future and second fieldwork, with questionnaires with questions related to water supply services in 60 residences in a random way, in order to understand why there exist in the municipality these two supplier companies, Casal and Samae and why users' dissatisfaction with them. The results show that some parameters found in the samples are in disagreement with Ordinance No. 2,914, dated December 12, 2011 of the Ministry of Health, which deals with the procedures for controlling and monitoring the quality of water for human consumption and its standard of potability. It can be concluded that water supply and treatment systems are not sufficient for the Ibateguarian population, requiring a better attention from the public power.